2011
DOI: 10.2217/whe.11.65
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Safety and Health-Related Quality of Life in Women with Heavy Menstrual Bleeding Treated with Oral Tranexamic Acid

Abstract: Long-term TA treatment was well tolerated and improved measures of HRQoL in women with cyclic HMB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Another study indicated that HRQL improved in women with menorrhagia and abnormal laboratory hemo stasis when they were treated with either tranexamic acid or intranasal desmopressin; tranexamic acid proved to be more effective [16]. Recent studies have shown that TA, in addition to reducing mean MBL per cycle, also has a positive impact on HRQL [12][13][14] as measured by the validated Menorrhagia Impact Questionnaire (MIQ) [17].…”
mentioning
confidence: 99%
“…Another study indicated that HRQL improved in women with menorrhagia and abnormal laboratory hemo stasis when they were treated with either tranexamic acid or intranasal desmopressin; tranexamic acid proved to be more effective [16]. Recent studies have shown that TA, in addition to reducing mean MBL per cycle, also has a positive impact on HRQL [12][13][14] as measured by the validated Menorrhagia Impact Questionnaire (MIQ) [17].…”
mentioning
confidence: 99%
“…It improves symptoms of HMB generally within three cycles, reducing menstrual blood flow by 29–58% (Lethaby et al , ; Lukes et al , ). If effective, it can be used long term (Muse et al , ). Tranexamic acid improves HRQL, haemoglobin and ferritin levels in women with HMB (Winkler, ; Lukes et al , , ; Muse et al , , ).…”
Section: Managementmentioning
confidence: 99%
“…If effective, it can be used long term (Muse et al , ). Tranexamic acid improves HRQL, haemoglobin and ferritin levels in women with HMB (Winkler, ; Lukes et al , , ; Muse et al , , ). The risk of thrombosis is controversial.…”
Section: Managementmentioning
confidence: 99%
“…TA is a Food and Drug Administration-approved hemostatic agent for the treatment of traumatic bleeding and is also available over-the-counter elsewhere for indications such as heavy menstrual bleeding (Dunn and Goa, 1999;McCormack, 2012). As a hemostatic agent, TA is reported to have a favorable safety profile for existing indications Muse et al, 2011) and has been demonstrated as an inexpensive and effective treatment for traumatic bleeding, as suggested recently by the multicenter Clinical Randomization of an Antifibrinolytic in Significant Hemorrhage-2 trial (Roberts et al, 2011). In agreement with our findings in plasminogen-null mice, administration of TA also attenuated acetaminophen hepatotoxicity in mice, albeit to a lesser extent (Sullivan et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%